Investigation on Erosion Intensity of Production Roads Under "7·13" Rainstorm in 2020 — Taking Wushicha Small Watershed at Xiji County, Ningxia Hui Autonomous Region as an Example - Siyu Yan; Binbin Li; Kunxia Yu; Peijuan Cong; Ning Dai (Shuitu baochi tongbao)
[Objective] The erosion intensity and the causes of erosion of the production roads after rainstorm in the small watershed at Xiji County, Ningxia Hui Autonomous Region were explored in order to provide a theoretical basis for improving the situation of soil erosion and improving the construction and maintenance of water and soil conservation projects in the future. [Methods] From July 25 to 29, 2022, Soil and Water Conservation Monitoring Center of the Ministry of Water Resources organized a comprehensive survey on soil and water conservation of the "7·13" rainstorm at Xiji County, Ningxia Hui Autonomous Region. The environment and erosion status of the production road in the small watershed of the Wushicha small watershed were investigated and the erosion intensity was calculated by using the "section method". The erosion intensity status and the causes of erosion were analyzed. [Results] ① The rainfall, the characteristics of road and the human activities are the main influencing factors of the production roads erosion in the Wushicha small watershed. Each road shows different erosion patterns, among which the lower reaches of the small watershed, along the runoff direction and with low vegetation coverage are seriously eroded. ② The road erosion modulus of small watershed is analyzed and calculated. The calculated value of "section method" is 1 054.49 t/km2, and the measured value of 3D image is 1 277.91 t/km2. The damage rate of the survey section is 53.39%. [Conclusion] It is necessary and effective to implement soil and water conservation measures. Good soil and water conservation measures and high vegetation coverage rate can effectively prevent the occurrence of soil and water loss on production roads.